The Investigation of Mobility Levels of Postoperative Patients Open Heart Surgery and Influencing Factors - Çınar, Fadime (Iris Publishers LLC, 2020)
Objective: The aim of this study was to investigate the mobility levels of the patients who had open heart surgery and ınfluencing factors the postoperative period. Method: This is a descriptive cross-sectional study. The study sample consisted of 118 patients who had open heart surgery in a cardiovascular surgery clinic of a cardiovascular surgery training hospital. The study was conducted between October and December 2018 in a 3-month period. The mobility difficulties experienced by the patients and their activity levels during the postoperative period were evaluated using the Patient Mobility Scale and the Observer Mobility Scale. The data were analyzed using SPSS 25.0 software. Results: 41.7% of patients returned to the other side of the bed, 36.3% had to sit on the edge of the bed and 32.8% had oral warning and physical help while walking in the room, while 27.4% stand up independently with verbal warning on the edge of the bed. they were able to get up. The results showed that the patients were unable to turn independently from one side of the bed to the other. Conclusion: The findings of this study are significant in order to show that the patients who have undergone open heart surgery to increase the level of movement in early postoperative period will have a positive effect on the overall recovery process of the patients
Keywords: Postoperative period; Open heart surgery; Moving the patient; Early standing up